Credit Channel Transmission of Monetary Policy: How Promote Growth in Indonesia? - Wulandari, Evalia; Astuti, Rini Dwi (Journal of International Conference Proceedings, 2023)
Credit plays a significant part in supporting the public economy and as a driver of financial development. Banking facilitates households and companies as deficit spending units to finance their consumption and investment. This encourages the economic growth through increased aggregate demand. This research aims to analyze the transmission of monetary policy in Indonesia through credit channel, how the monetary policy affects economic growth. For monthly data 2017-2022, with the Vector Error Correction Model (VECM) and Vector Auto Regressive (VAR), the research results show that economic growth provides a negative response to consumption shocks on the household liquidity effect credit channel. While through the balance sheet channel, economic growth responds positively to investment shocks.  The balance sheet channel is more effective in transmitting monetary policy credit channels targeting economic growth in Indonesia during the research period. Investment as an engine of growth is achieved through optimizing the role of banking intermediation in productive rather than consumer financing because it has a greater multiplier effect on the economy.